Analysis of Pediatric Pulpotomy, Pulpectomy, and Extractions in Primary Teeth Revealed No Significant Association with Subsequent Root Canal Therapy and Extractions in Permanent Teeth: A Retrospective Study - Arash Farhadian; Mayce Arreem Issa; Karl Kingsley; Victoria Sullivan (MDPI AG, 2024)
Recent evidence suggests that an ever-growing number of pediatric patients require invasive treatments such as root canal therapy (RCT) in their permanent dentition, albeit with little information about risk factors such as prior invasive treatments of pulpotomy or pulpectomy in their primary dentition. Therefore, the primary objectives of this study were to determine the number of pediatric patients who have had any type of invasive treatment in their primary teeth, to assess their association with any subsequent invasive treatment (root canal therapy, extractions) in their permanent dentition, and to assess these trends over time. This retrospective study utilized summary data from a clinical pediatric patient pool (ages 0-17) over the period of 2013-2022. This analysis revealed that pediatric patients requiring pulpotomies and pulpectomies in primary dentition declined between 2013 (n = 417, n = 156) and 2022 (n = 250, n = 12), while root canal therapy (RCT) in permanent dentition increased six-fold from n = 54 to n = 330. In addition, few (7.8%) patients with RCT had a previous history of pulpotomy or pulpectomy, which suggests that invasive treatments performed in primary dentition have no direct association with the subsequent need for invasive treatments in permanent dentition, although more research is needed to determine the explanations for these observations.